2015
DOI: 10.1177/0192513x15581659
|View full text |Cite
|
Sign up to set email alerts
|

Stigma as a Barrier to Substance Abuse Treatment Among Those With Unmet Need: An Analysis of Parenthood and Marital Status

Abstract: Substance use (SU) stigma is one factor contributing to unmet need for SU treatment. Additionally, theory suggests that women and single parents who use substances experience enhanced stigma because they do not adhere to normative social expectations. This study examines differences in perceived stigma by gender and parenthood among those with unmet need for SU treatment using the 2003-2010 National Survey of Drug Use and Health ( = 1,474). Results indicate that women are more likely to report stigma as a barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(99 citation statements)
references
References 72 publications
7
87
0
5
Order By: Relevance
“…In addition to the impact on help-seeking behaviors, stigma is also thought to impact the quality of healthcare services delivered by medical professionals (van Boekel et al, 2013), as well as the services suggested in a treatment plan by substance use treatment professionals (Kelly and Westerhoff, 2010). Thus, stigma presents as a formidable barrier to engaging with SUD treatment (Stringer and Baker, 2015; Clement et al, 2015; Stone, 2015), the recommendation of SUD treatment services (Kelly and Westerhoff, 2010), and the quality of services delivered once engaged (van Boekel et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the impact on help-seeking behaviors, stigma is also thought to impact the quality of healthcare services delivered by medical professionals (van Boekel et al, 2013), as well as the services suggested in a treatment plan by substance use treatment professionals (Kelly and Westerhoff, 2010). Thus, stigma presents as a formidable barrier to engaging with SUD treatment (Stringer and Baker, 2015; Clement et al, 2015; Stone, 2015), the recommendation of SUD treatment services (Kelly and Westerhoff, 2010), and the quality of services delivered once engaged (van Boekel et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this paper, informal help‐seeking is defined as parents' disclosing and seeking assistance for their alcohol misuse and parenting challenges from within their informal networks, including immediate and extended family, friends, neighbours, colleagues or fellow substance misusers attending informal treatment (Broadhurst, ; Stringer and Baker, ; Thompson, ). Informal support networks vary in their level of knowledge and capacity to support substance‐misusing parents adequately and address the range of associated risk factors often present for these families (Thompson, ).…”
Section: Defining Help‐seekingmentioning
confidence: 99%
“…A key barrier to help‐seeking in the context of substance misuse is perceived or experienced stigma associated with substance misuse (Jackson and Shannon, ; Lloyd, ). For parents, perceiving services as non‐judgemental and non‐stigmatising seems to be a key factor in encouraging help‐seeking, especially from formal resources such as specialised substance misuse and family welfare services (Broadhurst, ; Gueta, ; Stringer and Baker, ). On account of persistent gender stereotypes, this stigma may be more pronounced in mothers than fathers owing to substance misuse being perceived as more deviant for women who are generally the primary carer of young children (Gueta, ; Stringer and Baker, ; Verissimo and Grella, ).…”
Section: Factors Impacting Help‐seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, substance abuse may negatively affect parental sensitivity and monitoring, resulting in less reliable or late problem recognition (Elkins, McGue, Malone, & Iacono, 2004;Robertson, Baird-Thomas, & Stein, 2008). In addition, societal stigmatization of substance-abusing parents can be a hampering factor for these parents when it comes to seeking help and being open with professionals about their personal and family problems (Stringer & Baker, 2015). Fear that openness might lead to negative consequences, such as losing custody of their children, increases parents' reluctance to seek or accept help.…”
mentioning
confidence: 99%